IMPLEMENTASI PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH DI SMPIT HIDAYAH KLATEN - STEELYANA INDRIA SARI; RAVI SUCI SAPUTRO (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2023)
This study was describe management implementation of The School Operational Assistance Fund (BOS) in SMPIT Hidayah Klaten. The data collection was done through observation, interview and documentation study. The data analysis used in this study were data reduction, data presentation, and conclusion drawing. The result show that 1) the planning, implementation, supervision, and reporting process of Dana BOS management in SMPIT Hidayah Klaten in 2020 has run well according to the technical guidelines of Permendikbu (Ministerial Regulation of Education and Culture) Number 8 of 2020, 2) the obstacles in managing Dana BOS in SMPIT Hidayah Klaten were the disbursement of funds was often delayed and there were also regulation changes in the School Operational Assistance Management. The efforts undergone to overcome the obstacles were done by the management team in SMPIT Hidayah Klaten who have to borrow loans from the corporate partner and related to the changes in the government regulations, the financial management team re-compile LPJ (the accountability report) according to the new Permendikbud technical instructions. ABSTRAKPenelitian ini deskriptif implementasi pengelolaan dana bantuan operasional sekolah di SMPIT Hidayah Klaten. Teknik pengumpulan data dilakukan melalui observasi, wawancara dan studi dokumentasi. Teknik analisis data yang digunakan yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa 1) Proses Perencanaan, Pelaksanaan, Pengawasan, dan Pelaporan Pengelolaan Dana BOS di SMPIT Hidayah Klaten telah berjalan dengan baik sesuai dengan petunjuk teknis Peraturan Menteri Pendidikan dan Kebudayaan (Permendikbud) Nomor 8 Tahun 2020, 2) Kendala pengelolaan dana BOS di SMPIT Hidayah Klaten yaitu waktu pencairan dana sering mengalami keterlambatan dan juga terdapat perubahan peraturan pengelolaan dana BOS. Upaya mengatasi kendala dilakukan bon di tempat rekanan yang sudah diajak kerjasama dan terkait perubahan aturan pemerintah, tim pengelolaan keuangan dana BOS melakukan penyusunan laporan pertanggungjawaban (LPJ) ulang sesuai dengan petunjuk teknis Permendikbud yang baru.